CuxO and carbon–modified TiO2–based hybrid materials for photocatalytically assisted H2 generation. (March 2021) - Tobaldi, D.M.; Kočí, K.; Edelmannová, M.; Lajaunie, L.; Figueiredo, B.; Calvino, J.J.; Seabra, M.P.; Labrincha, J.A.
Abstract: Hydrogen, as an energy carrier, is a zero-emission fuel. Being green and clean, it is considered to play an important role in energy and environmental issues. Photocatalytic water splitting is a process used to generate hydrogen from the dissociation of water. Titanium dioxide is the archetype material for photocatalytic water splitting. However, because of the fast recombination of the photo-generated exciton, the yield of the reaction is typically low. To overcome this limit, in this work, the surface of the TiO2 nanoparticles was modified with copper and graphene to give hybrid nanostructures. Synthesized materials were tested in the photocatalytic hydrogen generation using methanol as the sacrificial agent. X-ray diffraction and spectroscopic results showed that copper did not enter the TiO2 structure, and that neither copper nor graphene substantially altered the optical band-gap of prepared photocatalysts. Detailed aberration-corrected high-resolution electron transmission electron imaging and spatially resolved energy-loss spectroscopy experiments showed the oxidation and amorphization of graphene nanoplatelets, probably due to the combined action of the acidic media of the solution with the thermal treatment necessary to produce the hybrid materials. Hydrogen generation from methanol/water mix proved that exists an optimum concentration of both copper and graphene (i.e. 0.5 mol% copper plus 0.5 wt% graphene) to grant a two-fold increase in hydrogen production compared with that of unmodified titania when using UVA irradiation. A higher amount of initial graphene (i.e. 1.0 wt% graphene and 0.5 mol% copper) was instead necessary for granting higher H2 generation on visible-light exposure. Hybrid materials based on titania modified with both copper oxide and carbon-based materials could therefore be exploited as ideal candidates for light-to-energy applications. Graphical abstract: Image 1 Highlights: Copper and copper plus graphene nanoplatelets to make TiO2 -based hybrids. Synthesis led to a partial amorphization and oxidation of graphene nanoplatelets. Dynamic and complex system under light exposure (UVA and visible). Continuous reduction of Cu(II) to Cu(I) under light irradiation due to IFCT. Optimum amount of Cu x O and carbon materials (0.5 mol% and 0.5 wt%) to improve H2 generation.